92PProspective randomized controlled study comparing primary surgery versus neoadjuvant chemotherapy followed by surgery in gastric carcinoma. (24th November 2019) - Goel, V
Abstract: Background: Neoadjuvant chemotherapy in gastric cancer can treat micro metastatic disease and can increase the resectability rate. The trial was to compare early outcomes after primary surgery versus neoadjuvant chemotherapy followed by surgery in gastric adenocarcinoma. The primary aim of the study was to compare resectability and R0 resection rates in upfront surgery v/s chemotherapy followed by surgery arm. A secondary aim was to see if neoadjuvant chemotherapy is well tolerated or not by comparing postoperative morbidity and mortality. Methods: The study consisted of 60 consecutive patients of carcinoma stomach randomized into primary surgery and neoadjuvant chemotherapy followed by surgery arms. Morbidity, pathological status, and mortality data were collected and analyzed. Results: Mean operating time in primary surgery arm was 290 ± 46.5 min, while in NACTarm, it was 316.7 ± 56.6 min, respectively. When postop complications were compared between the arms, it was not significant. Comparing the histopathological report of two groups, there was no significant difference between differentiated, T stage, mean lymph node harvest, R0 resection, PNI, and LVI. Conclusions: Neoadjuvant chemotherapy showed a trend towards improving in the R0 resection rate. There is no increase in postoperative morbidity and mortality with neoadjuvant chemotherapy. Legal entity responsible for the study: The author. Funding: Has not received any funding. Disclosure: The author has declared no conflicts of interest.